Kurt Baschwitz A Pioneer of Communication Studies and Social Psychology - van Ginneken, Jaap (Amsterdam University Press, 2018)
Kurt Baschwitz (1886-1968) had a lifelong fascination for 'the riddle of the mass' in both its visible and invisible forms. He was a major pioneer of communication and media studies on the European continent, an early student of the social, political, and mass psychology of crowds, publics, audiences, and public opinion, as well as a versatile social historian. Half a century after his death, however, he risks being forgotten and misunderstood, falling through the cracks of history.